Synthetic niches for differentiation of human embryonic stem cells bypassing embryoid body formation. Issue 5 (10th December 2013) - Liu, Yarong; Fox, Victoria; Lei, Yuning; Hu, Biliang; Joo, Kye‐Il; Wang, Pin
Abstract The unique self‐renewal and pluripotency features of human embryonic stem cells (hESCs) offer the potential for unlimited development of novel cell therapies. Currently, hESCs are cultured and differentiated using methods, such as monolayer culture and embryoid body (EB) formation. As such, achieving efficient differentiation into higher order structures remains a challenge, as well as maintaining cell viability during differentiation into homogeneous cell populations. Here, we describe the application of highly porous polymer scaffolds as synthetic stem cell niches. Bypassing the EB formation step, these scaffolds are capable of three‐dimensional culture of undifferentiated hESCs and subsequent directed differentiation into three primary germ layers. H9 hESCs were successfully maintained and proliferated in biodegradable polymer scaffolds based on poly (lactic‐co‐glycolic acid) (PLGA). The results showed that cells within PLGA scaffolds retained characteristics of undifferentiated pluripotent stem cells. Moreover, the scaffolds allowed differentiation towards the lineage of interest by the addition of growth factors to the culture system. The in vivo transplantation study revealed that the scaffolds could provide a microenvironment that enabled hESCs to interact with their surroundings, thereby promoting cell differentiation. Therefore, this approach, which provides a unique culture/differentiation system for hESCs, will find its utility in various stem cell‐based tissue‐engineering applications. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 102B: 1101–1112, 2014.